Prevalence and grade of diabetic peripheral neuropathy among known diabetic patients in rural Uganda - Munyambalu, Dalton Kambale; Hildago, Idania; Bafwa, Yves Tibamwenda; Lagoro, Charles Abonga; Sikakulya, Franck Katembo; Vahwere, Bienfait Mumbere; Dafiewhare, Ephraim; Martinez, Lazaro; Charles, Fardous Abeya (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background Diabetic peripheral neuropathy (DPN) is the most common complication of diabetes mellitus (DM). Approximately 50% of diabetic patients are estimated to develop DPN, depending on disease duration and diabetic control. Early diagnosis of DPN will avoid complications, including non-traumatic lower limb amputation, which is considered the most debilitating complication, as well as significant psychological, social, and economical problems. There is a paucity of literature on DPN from rural Uganda. This study aimed to deliver the prevalence and grade of DPN among DM patients in rural Uganda. Methods A cross-sectional study that recruited 319 known DM patients was conducted in an outpatient clinic and a diabetic clinic at Kampala International University-Teaching Hospital (KIU-TH), Bushenyi, Uganda, between December 2019 and March 2020. Questionnaires were used to obtain clinical and sociodemographic data, a neurological examination was carried out to assess the DPN, and a blood sample was collected from each participant (for random/fasting blood glucose and glycosylated hemoglobin analyses). Data were analyzed using Stata version 15.0. Results The sample size was 319 participants. The mean age of study participants was 59.4 ± 14.6 years and there were 197 (61.8%) females. The prevalence of DPN was 65.8% (210/319) (95% CI 60.4% to 70.9%), and 44.8% of participants had mild DPN, 42.4% had moderate DPN, and 12.8% had severe DPN. Conclusion The prevalence of DPN at KIU-TH was higher among DM patients and its stage might have a negative impact on the progression of Diabetes Mellitus. Therefore, clinicians should consider neurological examination as a routine during assessment of all DM patients especially in rural areas where resources and facilities are often limited so that complications related to Diabetic mellitus will be prevented.